Serum, Saliva, and Urine Irisin with and Without Acute Appendicitis and Abdominal Pain - Bakal, Unal; Aydin, Suleyman; Sarac, Mehmet; Kuloglu, Tuncay; Kalayci, Mehmet; Artas, Gokhan; Kazez, Ahmet (Sage Publications Ltd, 2016)
A 112-amino-acid protein irisin (IRI) is widely expressed in many organs, but we currently do not know whether appendix tissue and blood cells express it. If appendix tissue and neutrophil cells express IRI, measuring its concentration in biological fluids might be helpful in the diagnosis of acute appendicitis (AA), since neutrophil cells are the currently gold-standard laboratory parameters for the diagnosis of AA. Therefore, the purpose of this study was to investigate the suitability of enzyme-linked immunosorbent assay-based measurements of the proposed myokine IRI for the discrimination of patients with AA from those with acute abdominal pain (AP) and healthy controls. Moreover, immunoreactivity to IRI was investigated in appendix tissues and blood cells. Samples were collected on admission (T1), 24 hours (T2), and 72 hours (T3) postoperatively from patients with suspected AA and from patients with AP corresponding to T1-T3, whereas control subject blood was once corresponding to T1. IRI was measured in serum, saliva, and urine by using enzyme-linked immunosorbent assay, whereas in appendix tissue and blood cells, IRI was detected by immunohistohcemistry. Appendix tissue and blood cells (except for erythrocytes) are new sources of IRI. Basal saliva, urine, and serum levels were higher in children with AA compared with postoperative levels (T2) that start to decline after surgery. This is in line with the finding that IRI levels are higher in children with AA when compared with those with AP or control subject levels, most likely due to a large infiltration of neutrophil cells in AA that release its IRI into body fluids. Measurement of IRI in children with AA parallels the increase or decrease in the neutrophil count. This new finding shows that the measurement of IRI and neutrophil count can together improve the diagnosis of AA, and it can distinguish it from AP. IRI can be a candidate marker for the diagnosis of AA and offers an additional parameter to neutrophil count. The promising receiving operating curve results indicate the following sensitivities and specificities, respectively, for IRI: serum 90% and 55%, saliva 90% and 60%, and urine 90% and 50%. Serum neutrophil count gave a sensitivity of 90% and a specificity of 90%. This promising result now needs to be confirmed in a larger group of patients.
Keywords: serum; saliva; urine; irisin; acute appendicitis